1996
DOI: 10.1002/(sici)1097-4652(199608)168:2<264::aid-jcp5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protein abundance in pluripotent cells undergoing commitment to the neural lineage

Abstract: The P19 cell line is a widely studied model of neural differentiation When pluripotent P19 cells are cultured as aggregates in the presence of retinoic acid for 4 days, the cells commit to the neural fate, but have not yet undergone overt differentiation. Two-dimensional polyacrylamide gel electrophoresis was used to analyze cellular protein expression during this induction. Approximately 500 abundant polypeptides were analyzed. Seventeen polypeptides were upregulated during induction; several of these were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…6 A similar 2DE analysis of protein abundance in P19 cells undergoing neuronal development revealed 500 abundant polypeptides, 17 of which were regulated. 7 However, this early study did not identify many of these proteins. A subsequent study of P19 cell neural differentiation identified only 28 differentially expressed proteins.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…6 A similar 2DE analysis of protein abundance in P19 cells undergoing neuronal development revealed 500 abundant polypeptides, 17 of which were regulated. 7 However, this early study did not identify many of these proteins. A subsequent study of P19 cell neural differentiation identified only 28 differentially expressed proteins.…”
Section: Introductionmentioning
confidence: 89%
“…A study of the in vitro differentiation of adult rat hippocampal neural stem cells by two-dimensional electrophoresis (2DE), resulted in the identification of 367 regulated spots, of which 128 could be identified, although many of these proteins were isoforms . A similar 2DE analysis of protein abundance in P19 cells undergoing neuronal development revealed 500 abundant polypeptides, 17 of which were regulated . However, this early study did not identify many of these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…This model closely resembles events occurring during mammalian embryogenesis [1,9,26,30,39]. Exposure of P19 EC cells to RA gives rise to a population of dierentiating neurons and, later, to astrocytes that express similar developmental markers as their embryonic counterparts [36]. The polysialylated form of NCAM (PSA-NCAM), the product of an NCAM-speci®c PSA synthase (ST8Sia II/STX), can serve in this in vitro model as an early indicator of neuronal dierentiation [4,17].…”
Section: Discussionmentioning
confidence: 85%
“…The proteomics approach is a powerful tool to find clues to investigate the mechanism of a biological process due to its capability of resolving thousands of proteins at one time. The first proteomic analysis of P19 cell aggregation was carried out by Ray and Gottlieb in 1996, 20 when they tried to find differentially expressed protein spots between aggregated and nonaggregated P19 cells in their 2DE gels, but they failed to reveal any aggregation-related proteins, probably due to technical limitations. Advances in 2DE technology and peptide mass spectrometry offer a promising proteomic approach to study cell aggregation during P19 cell neural differentiation.…”
Section: Introductionmentioning
confidence: 99%